Changes in physicochemical properties and bacterial communities in aged Korean native cattle beef during cold storage. Issue 8 (1st April 2022) - Hwang, Sun Hye; Lee, JaeHwan; Nam, Tae Gyu; Koo, Minseon; Cho, Yong Sun
Abstract: During refrigerated storage, aged beef is liable to undergo alterations in its physicochemical properties. This study aimed to evaluate changes in the community of microorganisms, volatile compounds, and amino acids in aged beef under cold storage conditions. In addition, volatile basic nitrogen (VBN) values were measured to determine the putrefaction degree. Raw‐, dry‐, and wet‐aged beef were stored at 4°C for 21 days. The initial pH of beef under the three conditions ranged from 5.52 to 5.60 and decreased from 5.04 to 5.33 over time. After 21 days, VBN values ranged 20.53–22.59 mg/100 g, which exceeded the standard of spoilage (20 mg/100 g) in the Korean Food Code. As time passed, numbers of psychrophilic and lactic acid bacteria increased in the raw beef. In contrast, number of mesophilic, psychrophilic, and lactic acid bacteria decreased in dry‐ and wet‐aged beef. Among the volatile substances and amino acids, 2, 3‐butanedione, 2‐butanone, tyrosine, and arginine contributed the most to the high VBN levels in aged beef, where the VBN was 21 mg/100 g at 21 days, which was beyond the acceptable limit. In conclusion, clear alterations were observed in the physicochemical properties and microorganism communities in cold‐stored aged beef, providing basic information that could benefit the beef industry and boost consumer acceptance. Abstract : Microbial, physicochemical changes due to refrigeration storage of aged Korean native cattle.